2011
DOI: 10.4103/0975-7406.84452
|View full text |Cite
|
Sign up to set email alerts
|

Role of family and peers in the initiation and continuation of smoking behavior of future physicians

Abstract: Background:Globally researchers have long back noted that the trend of substance use was on the rise particularly in the student population.Objective:To find out the prevalence and determinants of smoking practices among undergraduate medical students.Materials and Methods:A cross-sectional study was conducted among undergraduate medical (MBBS) students of a tertiary care medical college using a predesigned and pretested semi-structured self-administered anonymous questionnaire.Results:Among 182 participants, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
6
1
Order By: Relevance
“…In contrast to Basu et al (14) where parental smoking was found to be significantly associated with smokers; it was observed in the current study that most of the participants in the current study had no smokers in their family. This is probably because having smokers in the family have dual effects.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to Basu et al (14) where parental smoking was found to be significantly associated with smokers; it was observed in the current study that most of the participants in the current study had no smokers in their family. This is probably because having smokers in the family have dual effects.…”
Section: Discussioncontrasting
confidence: 99%
“…Quitting behaviour of those who made quit attempts Determinants for tabacco cessation amongst smokers visiting tertiary health care centre in IndiaHarakeh et al (13) and Basu et al(14) where interaction with smoking peer lead to initiation of smoking habit.…”
mentioning
confidence: 99%
“…In a study conducted in West Bengal ( 12 ), it was observed that 38% of the students have a familial history of smoking. This proportion was higher compared to that found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that the main factor contributing to smoking initiation in children and adolescents is peer pressure. 9 Other studies also support this finding. Several studies conducted in India observed that family members and peers not only hold a considerable influence on the initiation of smoking behavior, but are also an important source of spending money to buy cigarettes.…”
Section: Discussionmentioning
confidence: 66%